2020
DOI: 10.1093/eurpub/ckaa053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of introducing standardized packaging with larger health-warning labels in England: findings from adult smokers within the EUREST-PLUS ITC Europe Surveys

Abstract: Background The European (EU) Tobacco Product Directive (TPD) was implemented in May 2016 to regulate the design and labelling of cigarettes and roll-your-own tobacco. At the same time, the UK introduced standardized packaging measures, whereas Germany, Greece, Hungary, Poland, Romania and Spain did not. This study examines the impact of introducing standardized packaging in England using a quasi-experimental design. Methods D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Sub-group analysis, controlling for demographics and family and peer smoking, showed no association between harm ratings and smoking susceptibility. In a seven-country longitudinal survey, 22 there was no significant change between Wave 1 (transition period) to Wave 2 (post-standardized packaging) in the percentage of participants in England who reported that their own brand was no different in harmfulness compared to other brands (78.1% W1, 78.6% W2) or that their own brand was no smoother or harsher compared to other brands (30.4% W1, 32.6% W2).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Sub-group analysis, controlling for demographics and family and peer smoking, showed no association between harm ratings and smoking susceptibility. In a seven-country longitudinal survey, 22 there was no significant change between Wave 1 (transition period) to Wave 2 (post-standardized packaging) in the percentage of participants in England who reported that their own brand was no different in harmfulness compared to other brands (78.1% W1, 78.6% W2) or that their own brand was no smoother or harsher compared to other brands (30.4% W1, 32.6% W2).…”
Section: Resultsmentioning
confidence: 95%
“…Four studies, two quantitative 22 , 23 and two qualitative, 24 , 25 examined appeal. Participants were asked about different facets of appeal (eg, quality, prestige, coolness, popularity), either using no visual prompts or shown images of, or actual, standardized packs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results for both items were summed (range 0-6) and participants coded as light (0-1), moderate (2-3) or heavy smokers (4-6). [34][35][36][37] Those not providing valid answers for time to first cigarette were coded 'Not stated' for HSI category.…”
Section: Heaviness Of Smoking Indexmentioning
confidence: 99%